Using Inside-Out Open Innovation to Recover Abandoned Pharmaceutical Compounds - Henry Chesbrough (Journal of Innovation Management, 2015)
Pharmaceutical drug development costs have risen rapidly over the past twenty years.  However, the number of new molecular entities being approved has not increased.  As pharmaceutical companies scale back their R&D in light of this deteriorating productivity, significant unmet medical needs remain unaddressed.  Much of these rising costs can be traced to work on compounds that are abandoned before getting to market.  There is a growing need to recover these abandoned compounds. The inside-out branch of open innovation provides a way to increase the performance of pharmaceutical firms, both in addressing unmet societal needs, and potentially in identifying new revenue sources and business models for a more distributed model of commercializing new drugs.  This aspect of open innovation is not much discussed in the literature to date. The medical research community, in conjunction with a number of industry and nonprofit organizations, has started several projects to recover more abandoned compounds.  These new initiatives are still at an early stage, and have not received much critical evaluation to date.  Examining four of these initiatives, we find that they do extend the cognitive frames in the research phase, while doing less to extend those frames in the commercialization phase.